Total phenolic and flavonoid contents and free radical-scavenging capacity of Siamese neem flower extracts - Chaisawangwong, Worarat (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2009)
The free radical scavenging activity and the contents of total phenolic compounds and total flavonoids in the aqueous extracts of Siamese neem young flowers collected from 14 different locations in Thailand were determined. The aqueous extracts were purified by partition with butanol. The butanol extract contained total phenolic compounds and total flavonoids ranging from 59.86-120.61 mg gallic acid equivalent (GAE) and 28.03-74.18 mg rutin equivalent (RE) per gram butanol extract, respectively. EC 50 values determined by DPPH scavenging assay of the butanol extracts were within the range of 9.32-46.97 μg mL -1. Extracts from samples from the central area of Thailand had the strongest scavenging activity (average EC 50=18.33 μg mL -1), the highest total phenolic content (94.08 ± 19.09 mg GAE/g butanol extract) and total flavonoid content (60.08 ± 14.86 mg RE/g butanol extract). The results suggested correlation between the contents of total flavonoids and total phenolic compounds, and the scavenging activity of most extracts. The high free radical scavenging activity of Siamese neem young flower extracts supports the ethnomedical use of this plant.